2017
DOI: 10.1089/end.2016.0702
|View full text |Cite
|
Sign up to set email alerts
|

Comparing High-Intensity Focal Ultrasound Hemiablation to Robotic Radical Prostatectomy in the Management of Unilateral Prostate Cancer: A Matched-Pair Analysis

Abstract: In this matched pair analysis, HIFU hemiablation was comparable to RALP in controlling localized unilateral PCa, with no significant differences in the need for salvage therapies. HIFU was also associated to significantly better functional outcomes. Accurate patient selection remains vital, and larger prospective trials are needed to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 23 publications
1
51
0
1
Order By: Relevance
“…In other studies, 5‐year biochemical recurrence‐free survival rate in radical prostatectomy was 55.2%, 7‐year biochemical recurrence‐free survival rate in brachytherapy was 66% (with boost) versus 48% (without boost) in high‐risk patients . Although long‐term follow‐up data are not currently available, the oncological control in HIFU patients seems not significantly inferior to others, but shows better functional outcomes . We suggest that HIFU treatment can still be used in selective high‐risk patients.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In other studies, 5‐year biochemical recurrence‐free survival rate in radical prostatectomy was 55.2%, 7‐year biochemical recurrence‐free survival rate in brachytherapy was 66% (with boost) versus 48% (without boost) in high‐risk patients . Although long‐term follow‐up data are not currently available, the oncological control in HIFU patients seems not significantly inferior to others, but shows better functional outcomes . We suggest that HIFU treatment can still be used in selective high‐risk patients.…”
Section: Discussionmentioning
confidence: 57%
“…25 Although long-term follow-up data are not currently available, the oncological control in HIFU patients seems not significantly inferior to others, but shows better functional outcomes. [26][27][28] We suggest that HIFU treatment can still be used in selective high-risk patients.…”
Section: Discussionmentioning
confidence: 98%
“…[11][12][13][14][15][16][17] Third, the 4 studies reporting oncologic outcomes after hemiablation reported that repeat TRUS biopsy identified contralateral CaP in approximately 10% to 22% of patients. [31][32][33][34] In a similar baseline patient population, contralateral CaP was detected in 65% to 79% of prostatectomy specimens. [11][12][13][14][15][16][17]33 This finding highlights the potential for biopsy sampling error to overestimate the true efficacy of hemiablation, a shortcoming that we avoided by using WMP as the reference standard.…”
Section: Discussionmentioning
confidence: 91%
“…Currently, mechanical HIFU technology, as applied to prostate ablation, is predominately at the phase of preclinical animal studies . In the very first study in humans, prostate hypertrophy was treated by the cavitation histotripsy technique in 25 patients with an extracorporeal HIFU device (Vortx Rx [Histosonics, Inc, Ann Arbor, MI]) .…”
Section: Thermal Versus Mechanical Hifumentioning
confidence: 99%